2020
DOI: 10.1161/hypertensionaha.120.15885
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Strategy for Gut Microbiome-Based Diagnostic Screening of Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) is the number one leading cause for human mortality. Besides genetics and environmental factors, in recent years, gut microbiota has emerged as a new factor influencing CVD. Although cause-effect relationships are not clearly established, the reported associations between alterations in gut microbiota and CVD are prominent. Therefore, we hypothesized that machine learning (ML) could be used for gut microbiome–based diagnostic screening of CVD. To test our hypothesis, fecal 16S ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 45 publications
0
76
0
2
Order By: Relevance
“…Human gut microbiota is believed to be directly or indirectly involved in cardio-cerebrovascular disease (CVD) [ 1 ]. Although cause-effect relationships have not been established, the reported associations between gut microbiota and CVD alterations are prominent [ 2 ]. Studies [ 3 7 ] have shown that gut microbiota is associated with obesity, diabetes, dyslipidemia, and hypertension, which are risk factors for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Human gut microbiota is believed to be directly or indirectly involved in cardio-cerebrovascular disease (CVD) [ 1 ]. Although cause-effect relationships have not been established, the reported associations between gut microbiota and CVD alterations are prominent [ 2 ]. Studies [ 3 7 ] have shown that gut microbiota is associated with obesity, diabetes, dyslipidemia, and hypertension, which are risk factors for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Dysbiosis is frequently observed in cardiovascular diseases patients [ 25 , 26 ]. Dysbiosis is an “imbalance” in the gut microbial community.…”
Section: Microbiota and Dysbiosismentioning
confidence: 99%
“…The growing continuum of the development of computational intelligence methods like machine learning metamorphosizes the microbiological research and paves the way forward to digitalized microbiology [ 137 ]. The prolific application of machine learning has been visualized in last 5 years in microbiome studies that has focus on clarifying microbial taxonomy and their mutual interactions as well as also evaluating microbiome biomarkers of diagnosis of multiple diseases [ 138 ]. More recently, the efficacy of probiotic therapeutics has been evaluated by utilizing the ABIOME (A Bioreactor Imitation of the Microbiota Environment) utilizing machine learning algorithms at metabolome level [ 139 ].…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%